Anti-asthmatics prescriptions in the paediatric population in the Lazio Region of Italy: association with socio-demographic children’s and physician’s characteristics (Epidemiology, Biostatistics, and Public Health, 2022)
Background Asthma is the most common chronic disease in childhood; inItaly its prevalence is estimated to be 9% in children (0-14 years old).Objective Estimate the use of anti-asthmatics prescriptions in the paediatric population and to evaluate its association with children’s and physician’s characteristics.Methods The study was conducted in 728,830 children 1-14 years old residing in the Lazio region,Central Italy. Individual data on AA (ATC R03) prescriptions during 2009 were used. Prevalence was calculated according to children’s gender, age and area of residence.The association, in terms of rate ratio (RR), between AA prescription with children’s and physicians’ characteristics was estimated by multi level Poisson models.Results Overall, 404,239 AA prescriptions were given to 178,850 (25%) children with the highest frequency in the 1-2 age group (39%). Boys were more likely to receive a prescription than girls. Beclomethasone was the most prescribed active ingredient (34%), followed by salbutamol (24%); 44% of children ³6 years old had only 1 box prescription in the year, 48.9% of these subjects were treated with inhaled corticosteroids alone.Children’s gender, age and area of residence were the major determinants in drug prescription while, as far as physicians’ level,  gender and number of patients in charge were associated to a greater probability of getting an AA prescription.Conclusion Prescription data provide useful information to measure prevalence use and consumption of AA drugs. Variability between age groups as well as differences in doctors’ characteristics suggests that specific strategies to optimise resource use of AA are needed.